2013
DOI: 10.1002/iub.1184
|View full text |Cite
|
Sign up to set email alerts
|

Axin: An emerging key scaffold at the synapse

Abstract: Neurons communicate through neurotransmission at the synapse. Precise regulation of the synaptic structure and signaling during the formation and remodeling of synapses is vital for information processing between neurons. Scaffold proteins play key roles in synapses by tethering the signaling cascades spatially and temporally to ensure proper brain functioning.This review summarizes the recent evidence indicating that Axin, a scaffold protein, plays a central role in orchestrating presynaptic and postsynaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…9 597 and 521-663 in ZIP6 and ZIP10, respectively). Similar to known docking sites of GSK3 on axin 1 (AXIN1) and 2 (AXIN2)3334, these cytoplasmic loop segments within the two ZIP transporters are enriched in charged residues and C-terminally flanked by a histidine-rich segment. It has long been known that NCAM1 can be phosphorylated within its intracellular domain by casein kinase 1 (CK1) and GSK3 but in these early studies the phospho-acceptor site was not determined35.…”
Section: Discussionmentioning
confidence: 83%
“…9 597 and 521-663 in ZIP6 and ZIP10, respectively). Similar to known docking sites of GSK3 on axin 1 (AXIN1) and 2 (AXIN2)3334, these cytoplasmic loop segments within the two ZIP transporters are enriched in charged residues and C-terminally flanked by a histidine-rich segment. It has long been known that NCAM1 can be phosphorylated within its intracellular domain by casein kinase 1 (CK1) and GSK3 but in these early studies the phospho-acceptor site was not determined35.…”
Section: Discussionmentioning
confidence: 83%
“…In a separate study, it was demonstrated that Axin inhibition in a neuroblastoma cell line, through the application of Li (lithium) and a GSK-3β inhibitor, promoted neurite outgrowth, whereas ectopic Axin expression caused an opposite phenotype [43]. Subsequently, several reports have shown Axin's role in neuronal proliferation and differentiation, axon formation, dendritic spine morphology, and synapse formation [44][45][46][47][48].…”
Section: Vertebrate Modelsmentioning
confidence: 99%
“…(A) Intracellular protein Axin functions as a major scaffold for components of synapses, which include interactive glutamate receptors of the NMDA and AMPA types, bidirectional signaling by ephrin-B, and adhesive interactions through N-cadherin, the latter of which modulates gene transcription through β-catenin. Based on Wei et al (2010) and Chen et al (2013). (B) Expected crosstalk of Laminin (Ln)-induced signals, transferred to the intracellular milieu through PrP C -scaffolded mGluR1/5-, NCAM- and L1-mediated pathways.…”
Section: The Prion Protein As a Cell Surface Scaffold Proteinmentioning
confidence: 99%